Gypsy and Traveller Girls. Silence, Agency and Power - Roberta Piazza (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2022)
Review of the book Gypsy and Traveller Girls. Silence, Agency and Power, by Geetha Marcus.